ANALYSIS OF FACTORS OF NURSE COMPLIANCE IN THE APPLICATION OF STANDARD PRECAUTION TO THE PREVENTION OF COVID-19 - Muhammad, Safrullah; Muliana, Nyanyak (Universitas Respati Yogyakarta, 2022)
Corona Virus Disease 2019 (COVID-19) has spread around the world resulting in a very rapid increase in morbidity and can lead to death. Since the beginning of 2020 there has been an increase in the number of cases of COVID-19 virus infection. The ratio of deaths and exposure to COVID-19 for nursing personnel in Indonesia is among the highest compared to other countries. Therefore, efforts are needed to make